Technology Transfer for Anchovy Processing MSMEs in Pesisir Selatan Regency, West Sumatra - Mareta Kemala Sari; Isma Addi Jumbri; Nilmadesri Rosya; Calista Dash Ramadhani; M. Sabil Al Anshori (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2026)
Background: Small-scale fisheries micro, small, and medium enterprises (MSMEs) are vital to coastal livelihoods and local food systems in Indonesia. However, many anchovy-processing enterprises still rely on traditional methods with limited temperature control, non-food-grade equipment, and inadequate hygienic practices, resulting in inconsistent product quality and low processing efficiency. Contribution: This program demonstrates a participatory triple helix model involving government, academics, and fishermen groups to transfer appropriate fish-processing technology to coastal MSMEs. It supported Pandawa Jaya and Teri Sakato through food-grade equipment, temperature monitoring, gas-based heating, hygienic handling training, and value-added product mentoring. Method: A participatory community engagement approach was implemented through problem identification, needs assessment, solution design, technology introduction, hands-on training, continuous mentoring, and before-and-after evaluation. Results: The intervention replaced mixed-material boiling containers with food-grade stainless-steel vessels, introduced steam thermometers, and shifted heating from firewood to gas. Processing time decreased from 15 to 8 minutes, while production capacity increased from 10 to 13 kg per batch. Product quality improved through more uniform color, cleaner appearance, more consistent texture, and fewer processing defects. Conclusion: Community–university partnerships integrating appropriate technology, participatory training, and mentoring can improve food safety awareness, standardize processing practices, enhance production efficiency, and strengthen the sustainability and competitiveness of small-scale fisheries MSMEs.